Model characteristics of competitive activity of different skilled female volleyball players - Shchepotina, N. Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to determine and compare the model characteristics of competitive activity and an integrated assessment of highly qualified and skilled volleyball players.